Design and development of layer-by-layer based low-pressure antifouling nanofiltration membrane used for water reclamation - Li, Xin (2020)
Recent studies have confirmed the advantages of low-pressure nanofiltration (NF) membranes in integrated nanofiltration membrane bioreactor system followed by the reverse osmosis (RO) process for high recovery water reclamation. However, fouling of low-pressure NF membranes restricts their application in providing high quality feed to subsequent RO process. In this study, an antifouling low-pressure NF membrane was designed and fabricated via rapid co-deposition of polydopamine (PDA)/polyethylenimine (PEI) on electrostatic layer-by-layer (LBL) assembled polyethersulfone (PES) flat sheet membrane followed by crosslinking with glutaraldehyde. The optimized resultant membrane (LBL-cPP) presented approximately 11 LMH/bar pure water permeability with more than 90% rejection divalent cations under 2 bar pressure. The newly developed selective layer exhibited excellent antifouling performance and chemical stability ascribing to the inherent hydrophilicity of PDA/PEI and dual covalent reaction of PDA with the LBL layer. By feeding real municipal wastewater, the LBL-cPP membrane also achieved superior permeate quality, leading to lower RO fouling rate in subsequent RO unit as compared to commercial NF 270 membrane. Further organic foulant analysis indicated that 96.8% of dissolved organic carbons were effectively removed by the LBL-cPP membrane. Specifically, the novel NF membrane demonstrated high removal rate (>93%) for foulants with low molecular weights which was largely responsible for RO fouling, while maintaining the desired flux recovery rate and reduced cleaning frequency. This study demonstrates the potential of PDA/PEI modified low-pressure NF membranes in designing efficient and sustainable water reclamation technology.